Lessons Learn From Islamic Banking in Aceh: Analysis of The Emergence, Growth and Prospects of Single Banking Sistem - Jailani, Munawar Rizki; Bin Mohamad, Mohammad Taqiuddin; Danial, Danial (Universitas Islam Negeri Raden Intan Lampung, 2024)
Banking in Aceh, one of the provinces in Indonesia, has a unique system known as the single banking system. This article aims to explore the emergence, growth, and prospects of this system in Aceh. The research was conducted using primary and secondary data sources. Primary data was obtained through interviews with experts consisting of academics, bankers, and Islamic banking observers in Aceh. Meanwhile, secondary data was obtained from published and unpublished documents. The research results reveal that the Qanun for Sharia Financial Institutions introduced a single window system in Aceh in 2018. However, the implementation of this system faces significant challenges due to the lack of banking infrastructure and human resources. Despite its potential benefits, the prospects for a single banking system remain uncertain as it could lead to a monopoly of banking services, given the limited banking services currently available. Nevertheless, the single banking system has the potential to increase efficiency and simplify processes, making banking services more accessible and convenient for customers in Aceh.